2017
DOI: 10.1080/00207454.2017.1367682
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-frequency repetitive transcranial magnetic stimulation on reducing hemiplegic shoulder pain in patients with chronic stoke: a randomized controlled trial

Abstract: High-frequency rTMS could be used as a safe, beneficial therapeutic tool to manage HSP. We think it can be used as an adjuvant therapeutic modality to enhance the therapeutic outcome of HSP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 45 publications
0
38
0
2
Order By: Relevance
“…The VAS score decreased from 7 to 5.6 at 2 weeks and then to 3.9 at 8 weeks after rTMS treatment. Other observational studies that predominantly involved patients with CPSP (35, 37-39) also showed the analgesic effect of high-frequency rTMS stimulation (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Central Pain After Strokementioning
confidence: 84%
See 3 more Smart Citations
“…The VAS score decreased from 7 to 5.6 at 2 weeks and then to 3.9 at 8 weeks after rTMS treatment. Other observational studies that predominantly involved patients with CPSP (35, 37-39) also showed the analgesic effect of high-frequency rTMS stimulation (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Central Pain After Strokementioning
confidence: 84%
“…Five case studies (88,(90)(91)(92)94) also reported that rTMS reduced pain in patients with PLP after amputation. High-frequency rTMS stimulation (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) Hz, mainly to the DLPFC) and low-frequency stimulation (1 Hz, targets including the supplementary motor complex, primary somatosensory area, and primary sensory cortex) were performed, and significant the patients reported significant improvements in PLP.…”
Section: Phantom Painmentioning
confidence: 99%
See 2 more Smart Citations
“…Für HF-rTMS/M1 beim CRPS I wird weiterhin eine Empfehlung auf Evidenzlevel C gegeben [41]. Kürzlich wurde auch über eine signifikante Schmerzlinderung (25-30 %) bei Schulterschmerzen im chronischen Stadium nach Schlaganfall mit Hemiplegie berichtet, was bis zu 4 Wochen nach der rTMS anhielt [76]. Bei Phantomschmerz wurde rTMS/M1 kontralateral zum amputierten Glied appliziert [77], was eine signifikante Reduktion der Schmerzintensität von 30 % bis zu 2 Wochen nach der letzten rTMS zeigte.…”
Section: Andere Schmerzsyndromeunclassified